Effects of sales promotion on growth of deposits in national bank branches within Nairobi County - Kilonzi, Elijah Mulei (Meru: Elijah Mulei Kilonzi, 2015)
Most organisations use sales promotion in the line with the general believe that it induces immediate sale.However,positive effects are not guaranteed as negative and insignificant effects are noted in some instances.National Bank has been using sales promotion,particularly sales contests and sweepstakes to mobilize deposits since November 2013,but there were no empirical evidence to justify the continual usage.The study,based on Attention-Interest-Desire-Action(AIDA) model used non -experimental design and employed descriptive survey to determine the influence of sweepstakes and sales contests on growth on deposits in National Bank.The target population was 259 employees of National Bank in branches within Nairobi County,and the sample size for the study was 155 employees. Statistical Program me for Social Sciences (SPSS) programmed was used for ease of general analysis of the collected data,as well as in computation of regression analysis to determine the actual relationship between the techniques and deposit growth.The study found a high correlation between sales promotion and deposit growth(R=.863).Sales promotion in general was statistically significant (sin.<.0005) in predicting deposits growth and explained 74.5% of the variance in growth.Among the three techniques of sales promotion,only sweepstakes and sales staff contests were statistically significant (sig.<.0005) in predicting deposits growth and had positive influence on deposits.Non sales staff contest on the other hand was statistically insignificant(sig=2.42) in predicting deposits growth and had no influence on growth of deposits.The study concluded that sales promotion generally had positive effects on deposits,but some sales promotion techniques were ineffective in deposit mobilization.The study recommended for usage of sweepstakes and sales staff contests and discouraged usage of non-sales staff contests in mobilizing deposits.
Includes Appendix and Reference